(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides information about the historical development of the currently used literary language. The history of the Uzbek language, the emergence of the Uzbek ethnonym, the stages of its formation, and the researches of the Uzbek scholars who worked on them (including Makhmud Koshgari, Olim Mutallibov, Makhmud Zamakhshari, Alisher Navoi, Zakhiriddin Muhammad Babur and Aloyi Binni Muhibi) and Turkological scientists (Besim Atalay, Mukhammad Abdullah Turki) are discussed.